Nepal-Japan Relations and Implications for Nepal - Malla, Suresh (NCWA Annual Journal, 2026)
Nepal-Japan relations are crucial for both countries. The socio-cultural relations between Nepal and Japan are rooted in over a century of friendship. Nepal-Japan relations are significant and provide a rationale for studying them in the contemporary foreign policy of Nepal, given Japan’s increasing role in economic development and cultural prosperity. As Japanese aid to Nepal has no political agenda, it also supports Nepal’s cultural development. This article is intended to highlight Nepal’s socio-cultural relations with Japan. This research deals with Nepal-Japan relations as significant for cultural development. Based on secondary sources and employing descriptive and analytical methodologies, this study examines the historical evolution, political foundations, economic and educational cooperation, and socio-cultural dimensions of Nepal–Japan relations. It highlights both similarities and dissimilarities between the two nations while identifying emerging opportunities for enhanced bilateral cooperation. The study concludes that Nepal–Japan relations represent a stable, multidimensional partnership with strong potential for further expansion in political, economic, educational, and cultural spheres.